Search for New Targets of Deep Brain Stimulation for Epilepsy Treatment - Huang, Lili; van Luijtelaar, Gilles (Journal of Neurological Research And Therapy, 2016)
Although clinical trials in refractory epilepsy are currently carried out, the field of deep brain stimulation (DBS) in epilepsy is still at its initial stage. Little is known about where, when and how to stimulate and what would be the short and long consequences. Animal studies might provide clinicians with new ideas regarding targets for DBS. Here an overview is given regarding old and new targets in rodent models of temporal lobe epilepsy. The evidence from animal models showed that stimulation of the subiculum – either in responsive or scheduled manner - is anticonvulsant in different seizure and epilepsy models, indicating that the subiculum might be a promising candidate for DBS targets. For the rest, the antiepileptic effects of low frequency stimulation were established mostly in kindling models. The presence of a critical time window in which stimulation was effective following after discharges on kindling acquisition, demonstrates that timing of DBS is an important factor for the anticonvulsant effects of DBS.
Keywords: Deep Brain Stimulation; Epilepsy; Subiculum; Temporal Lobe Epilepsy; Kindling Model; Refractory Epilepsy